Teachers Facing Artificial Intelligence in a Public University in Northern Peru - Bernilla Rodriguez, Eduer Blandimiro (2024)
Artificial Intelligence (AI) is creating both opportunities and challenges in higher education. This article explores perceptions, concerns, barriers, and facilitators for integrating AI into academic activities. It focuses on a public university in Northern Peru, examining faculty opinions through interviews and focus groups. The findings show that faculty find generating texts and organizing activities with AI advantageous; however, some have concerns about its use, doubting its accuracy and truthfulness. They agree on discussing these changes and integrating them into the curriculum, seeking to overcome barriers through training to improve the perception and use of AI. Despite the potential and strong support of AI in the university, it is necessary to implement institutional measures.